Morbidity and Mortality in Rectal Surgery: A Study of 25 Cases - Hajri, Amal; Belbsir, Mohamed; Elwassi, Anas; Erguibi, Driss; Boufettal, Rachid; Rifki Jai, Saad; Chehab, Farid (European Scientific Journal, ESJ, 2024)
Rectal surgery is the only potentially curative treatment for many rectal pathologies, whether benign or malignant. However, post-operative complications can significantly impact the prognosis of patients. This retrospective study aimed to investigate morbidity and mortality among patients undergoing rectal cancer surgery over a two-year period at the Department of Digestive Cancer Surgery and Hepatic Transplantation of Ibn Rochd University Hospital (CHU) in Casablanca.". Among 62 patients, the average age was 61.98 years, with a female-to-male ratio of 1.5. Overall morbidity and mortality rates were 40.3% and 12%, respectively. Post-operative complications primarily included surgical site infections (40%) and urinary infections (20%), while long-term complications comprised incisional hernias (20%) and sexual problems (8%). The primary cause of mortality was intraoperative hemorrhage (8%). Factors influencing morbidity and mortality included age, BMI, comorbidities, type of intervention, and the benign or malignant nature of the pathology. Therefore, prevention involves preoperative identification of high-risk patients and enhanced perioperative care through multidisciplinary collaboration.